PENGARUH STRUKTUR KEPEMILIKAN SAHAM, KEPUTUSAN INVESTASI DAN PROFITABILITAS TERHADAP STRUKTUR MODAL DAN NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG LISTING DI BURSA EFEK INDONESIA - Ferdy Putra; Zulbahridar Zulbahridar (Jurnal Ekonomi, 2015)
This study aims to determine the effect of ownership structure (institutional ownership and managerial ownership), investment decisions and profitability on capital structure and firm value at Manufacturing companies in Indonesia Stock Exchange. Capital structure in this study is as an intervening variable Research conducted on a manufacturing company in Indonesia Stock Exchange in 2009-2012 observations. By using purposive sampling method, obtained a sample of 45 companies. Data were analyzed using path analysis.Based on the results of this study concluded that managerial ownership significant effect on firm value. institutional ownership does not affect the firm value. Investment decisions have a significant effect on firm value and profitability does not affect the firm value. variable capital structure is not able to be a moderating variables intervening variable for managerial ownership, institutional ownership, investment decisions and profitability of firm value